Physical activity when riding an electric-assisted bicycle with and without cargo - Martnes, Jørgen Jerstad; Bere, Elling (Frontiers in Sports and Active Living, 2023)
Background Regular physical activity provides several health benefits, and active transport is a convenient way to implement physical activity in everyday life. However, bikes’ lack of possibilities to carry cargo is a limitation. E-cargo bikes can help overcome barriers to cycling and increase levels of active transport while still providing the option to carry cargo such as groceries and children. As such, E-cargo bikes have a greater potential for being a substitute for cars, but relevance is not known as no study has assessed the energy expenditure and time used using E-cargo bikes with considerable cargo. Objectives The aim of this study is to compare time spent riding and exercise intensity when (1) riding an electric-assisted bicycle with cargo (30 kg) and without cargo and (2) driving a car. Method This study has a randomised crossover design. Eleven participants (six women) were recruited through convenience sampling. The participants traversed through a 4.5 km route with three different forms of transportation: an electric-assisted bicycle (E-bike) with 30 kg cargo, an E-bike without cargo, and a car. Oxygen uptake was measured with a portable oxygen analyser (Metamax 3B), and time spent cycling was measured on site by the test leader using a stopwatch. Results Riding an E-bike with cargo was slightly slower than riding an E-bike without cargo (11.8 vs. 11.1 min, p = 0.017) and driving a car (8.8 min, p = 0.002). There was no significant difference in exercise intensity between E-bikes with and without cargo but riding an E-bike with cargo entailed significantly higher exercise intensity compared to driving a car [4.9 metabolic equivalents of task (METs) vs. 1.4 METs, p ≤ 0.001]. Conclusions E-biking with cargo was rather similar in time spent and exercise intensity to E-biking without cargo, and not much slower than driving a car. Using E-cargo bikes, therefore, appears a good alternative to driving a car when in need of carrying things such as grocery bags and children, resulting in increasing physical activity and, at the same time, decreasing greenhouse gas emissions.